A liberdade em Jean-Jacques Rousseau - Medeiros, Maria de Fátima de Sousa (2019)
The French Revolution is the dominant success of the eighteenth century and its impetus, we believe, remains still these days. The intellectual force of France has caused the Enlightenment or time of reason to identify itself with the cause of French freedomJean-Jacques Rousseau, is regarded as one of the thinkers who marks an impulse of a kind of freedom focused on a nature of ethics State: Rousseau, was born in Geneva in 1712. From a family with few financial resources, an orphan of a mother still born and abandoned by his father in childhood, Rousseau was not fortunate to have a formal education. Voracious reader, especially of the great Latin authors such as Plutarch, experienced in literature, philosophy and contemplation of nature, as narrates in his autobiographical texts, the charms of a happy and solitary life. His adventurous spirit encouraged him, still in his adolescence, to abandon Geneva and travel across Europe. In France, he lived conflictuously with the main thinkers of his time – voltare, Diderot, Condilllac, D'Alembert and others – and produced his main works, where we will always find the notion of freedom from the state of nature of the man who was not Separate from himself and that has not become a thing in the course of history; The precursor of Romanticism, both for the subjects he dealt with and by his writing laden with feelings, critical of absolutism and the decadent morals of the nobility and bourgeoisie, wrote revolutionary works that marked the history of philosophy, literature, and Humanities: Discourse on the origin and fundamentals of Inequality among men, new Heloísa, the Social contract, Emilio; The confessions and the Devaneios of a lone walker. In view of the above, we can mention that the present dissertation has as the central object of study the conception of freedom in the work of the Thinker JeanJacques Rousseau. In the development of the research, an epistemological framework was attempted to clarify our way the thought of the philosopher on the issue of human freedom in the Natural state and in the Social State; For this purpose, we are worth the concept of freedom found in the work "the Social contract", in this sphere of political philosophy, we ask ourselves: what is the relationship between the criticism that Rousseau makes the degeneration of the man of the city with his proposal of freedom Policy? In order to respond to this inquiry, the dissertation was exposed in three moments, namely: first discussing the living conditions in the state of nature; In the second, it seeks to show the disruption of man with nature, demonstrating how it emerged from this break up inequalities as consequences of evolution; Then, in the third part, a reading of the work the Social contract is made to highlight the policy as a solution for human corruption.